Differences in psychological problems between low and high achieving students - Md Yasin, Md Aris Safree; Dzulkifli, Mariam Adawiah (BSRI Press, 2009)
This study was conducted to examine the differences between low and high achieving students in their psychological problems i.e. depression, anxiety, and stress. 120 undergraduate students of the International Islamic University Malaysia (IIUM) were involved in this study. The Depression Anxiety Stress Scale (DASS) was used to measure the level of depression, anxiety, and stress among students. Independent Sample T-test was used to differentiate the level of psychological problems between low and high achieving students. The findings of this study revealed that there were significant differences between low and high achieving students in their psychological problems. The findings of the study will be useful in assisting educators, counselors, psychologist, and researchers to develop strategies to enhance students’ psychological well-being.